TEISINIAI POŽIŪRIAI APIBRĖŽIANT PRIVATUMO IR VIEŠOJO INTERESO PUSIAUSVYRĄ - Lytvynenko, Anatoliy (Teisė, 2017)
The article encompasses a narrow topic in media law, namely the problem of utilization of personal data by media personnell, informational agencies as well as broadcasting enterprises. Since conventional personal data maintenance procedures expounded in appropriate data protection acts are almost explicitly exempt for journalistic, artistic or literary purposes, the issue of preserving a proper equipoise between the right to one’s privacy and the freedom of speech remains a crucial topic for analysis and theory assemblage.